Association of hysterectomy and invasive epithelial ovarian and tubal cancer: a cohort study within UKCTOCS. (17th October 2021) - Taylor, JA; Burnell, M; Ryan, A; Karpinskyj, C; Kalsi, JK; Taylor, H; Apostolidou, S; Sharma, A; Manchanda, R; Woolas, R; Campbell, S; Parmar, M; et al.
Abstract : Objective: To investigate the association between hysterectomy with conservation of one or both adnexa and ovarian and tubal cancer. Design: Prospective cohort study. Setting: Thirteen NHS Trusts in England, Wales and Northern Ireland. Population: A total of 202 506 postmenopausal women recruited between 2001 and 2005 to the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) and followed up until 31 December 2014. Methods: Multiple sources (questionnaires, hospital notes, Hospital Episodes Statistics, national cancer/death registries, ultrasound reports) were used to obtain accurate data on hysterectomy (with conservation of one or both adnexa) and outcomes censored at bilateral oophorectomy, death, ovarian/tubal cancer diagnosis, loss to follow up or 31 December 2014. Cox proportional hazards regression models were used to assess the association. Main outcome measures: Invasive epithelial ovarian and tubal cancer (WHO 2014) on independent outcome review. Results: Hysterectomy with conservation of one or both adnexa was reported in 41 912 (20.7%; 41 912/202 506) women. Median follow up was 11.1 years (interquartile range 9.96–12.04), totalling >2.17 million woman‐years. Among women who had undergone hysterectomy, 0.55% (231/41 912) were diagnosed with ovarian/tubal cancer, compared with 0.59% (945/160 594) of those with intact uterus. Multivariable analysis showed no evidence of an association between hysterectomy and invasive epithelial ovarian/tubal cancer (hazard ratio 0.98, 95% CI 0.85–1.13, P = 0.765). Conclusions: This large cohort study provides further independent validation that hysterectomy is not associated with alteration of invasive epithelial ovarian and tubal cancer risk. These data are important both for clinical counselling and for refining risk prediction models. Tweetable abstract: Hysterectomy does not alter risk of invasive epithelial ovarian and tubal cancer. Tweetable abstract: Hysterectomy does not alter risk of invasive epithelial ovarian and tubal cancer. Linked article This article is commented on by LF Wilson and SJ Jordan, p. 119 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16952 .